Chemodivergent reaction of azomethine imines and 2H-azirines for the synthesis of nitrogen-containing scaffolds. Issue 22 (22nd May 2019) - Wu, Yufeng; Tian, Bing; Hu, Chao; Sekine, Kohei; Rudolph, Matthias; Rominger, Frank; Hashmi, A. Stephen K.
Abstract : Metal-free reactions of 2 H -azirines with C, N -cyclic azomethine imines were investigated. Abstract : The metal-free reactions of 2 H -azirines with C, N -cyclic azomethine imines were investigated. N -Bridged strained ring-fused triazole derivatives or 1, 2, 4-triazine derivatives are obtained, and the chemoselectivity is dependent on the protecting group on the azomethine dipole. Although benzoyl-protected starting materials give access to strained polycyclic compounds, a ring-opening occurs in the case of a tosyl protecting group that is cleaved during the process with elimination of sulfinic acid. 1, 2, 4-Triazine can be prepared on a mmol-scale and concomitantly oxidized with air as an oxidant to form the corresponding ketone, which is an interesting structural motif that can be found in bioactive scaffolds.